2019
DOI: 10.1213/ane.0000000000003967
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study Examining the Association of Baseline Frailty and Postcardiac Surgery Delirium and Cognitive Change

Abstract: BACKGROUND: Frailty is a geriatric syndrome thought to identify the most vulnerable older adults, and morbidity and mortality has been reported to be higher for frail patients after cardiac surgery compared to nonfrail patients. However, the cognitive consequences of frailty after cardiac surgery have not been well described. In this study, we examined the hypothesis that baseline frailty would be associated with postoperative delirium and cognitive change at 1 and 12 months after cardiac surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
2
29
0
4
Order By: Relevance
“…with long-term cognitive changes. [49][50][51] Preliminary data even have suggested that the presence of delirium is more important than the severity of illness in predicting intensive care unit length of stay. 52 Delirium in the postoperative phase of cardiac surgical care occurs in all ages, affecting between 20% and 80% of patients.…”
Section: Goal-directed Fluid Therapy (Loe: I/cor: B-nr)mentioning
confidence: 99%
“…with long-term cognitive changes. [49][50][51] Preliminary data even have suggested that the presence of delirium is more important than the severity of illness in predicting intensive care unit length of stay. 52 Delirium in the postoperative phase of cardiac surgical care occurs in all ages, affecting between 20% and 80% of patients.…”
Section: Goal-directed Fluid Therapy (Loe: I/cor: B-nr)mentioning
confidence: 99%
“… 335 Prospective cohort study 76.8±8.1 CFS ‡‡‡ (Frail>5/7) CAM † Prevalence of frailty HR ‡ 0.21 (0.17 - 0.26) Prevalence of delirium HR ‡ 0.12 (0.09 - 0.16) Risk of delirium in frail patients RR § 3.79 (2.16 - 6.63) Alabaf Sabbaghi, et al, 2018 31 United Kingdom Emergency Sector To compare the clinical characteristics, frailty, dementia and delirium in a hospital with a specialized counseling team for frail older adults versus usual treatment. 6,191 Retrospective and documentary 84.6±6.3 CFS ‡‡‡ 4-ATM §§§ Prevalence of frailty HR ‡ 0.05 (0.04 - 0.06) Prevalence of delirium HR ‡ 0.12 (0.11 - 0.13) Nomura, et al, 2018 32 Japan Cardiac surgery To examine the hypothesis that baseline frailty would be associated with postoperative delirium and to cognitive changes from 1 to 12 months after a cardiac surgery. 133 Prospective cohort study Robust 69.3±7.9 Frail 73.4±8.09 Fried’s Phenotype CAM † and CAM-ICU |||||| Prevalence of frailty HR ‡ 0.34 (0.26 - 0.42) Prevalence of delirium HR ‡ 0.48 (0.40 - 0.56) Risk of delirium in frail patients RR § 1.04 (0.68 - 1.58) Goudzwaard, et al, 2018 33 Netherlands Cardiac surgery (TAVI ‡‡ ) To investigate the association between a new Erasmus Frailty Score and short- and long-term results after TAVI ‡‡ .…”
Section: Resultsmentioning
confidence: 99%
“…The scarcity of studies evaluating frailty as a predisposing factor to delirium 10 , 21 , 37 - 38 , 41 was an unexpected finding of this paper, as the association between these conditions is accepted in the clinical practice. No relationship was observed between frailty and development of delirium in seven of the 26 studies analyzed, (RR: 1; 95% CI: 0.51-1.98) 25 , (RR: 0.90; 95% CI: 0.36-2.23) 21 , (RR: 0.48; 95% CI: 0.26-0.87) 29 , (RR: 1.04; 95% CI: 0.68-1.54) 32 , (RR: 1.14; 95% CI: 0.85-1.53) 23 , (RR: 0.90; 95% CI: 0.84-0.98) 27 , (RR: 0.27; 95% CI: 0.17-0.43) 24 .…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis showed that FS and pre-frailty were associated with greater adjusted operative mortality and adjusted perioperative complications, and FS was associated with almost 5-fold risk of non-home discharge [ 49 ]. Preoperative FS also predicts prolonged respiratory therapy, prolonged stay in the intensive care unit, functional decline, postoperative delirium, reoperations, readmission rate, increased risk of institutional discharge, and early, mid-term, and late mortality [ 50 , 52 , 80 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ].…”
Section: Fs and Cardiac Surgery And Tavimentioning
confidence: 99%